1996
DOI: 10.1093/carcin/17.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical quantitation of 4-aminobiphenyl-DNA adducts and p53 nuclear overexpression in T1 bladder cancer of smokers and nonsmokers

Abstract: An immunoperoxidase method, using a monoclonal antibody which recognizes 4-aminobiphenyl (4-ABP)-DNA adducts, was developed for the detection and quantitation of DNA damage in bladder tissue and applied to stored paraffin blocks of transurethral resection specimens of 46 patients with T1 bladder cancer. Mean relative staining intensity for 4-ABP-DNA adducts was significantly higher in current smokers (275 +/- 81, n = 24) compared to nonsmokers (113 +/- 71, n = 22) (P < 0.0001). There was a linear relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 19 publications
3
31
0
1
Order By: Relevance
“…Unlike the protective effect seen with other variables, the association between p53 overexpression and ETS seems a logical one because human tumors associated with both direct and indirect exposure to tobacco carcinogens are frequently found to overexpress p53. 6,9 Studies in human populations have demonstrated the presence of DNA adducts with tobacco-related carcinogens in neoplasms associated with tobacco use, as well as in the oral mucosal cells of cancer-free tobacco users. 6,8,12 Similar studies would need to be conducted in feline populations to establish or deny a causative role for ETS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the protective effect seen with other variables, the association between p53 overexpression and ETS seems a logical one because human tumors associated with both direct and indirect exposure to tobacco carcinogens are frequently found to overexpress p53. 6,9 Studies in human populations have demonstrated the presence of DNA adducts with tobacco-related carcinogens in neoplasms associated with tobacco use, as well as in the oral mucosal cells of cancer-free tobacco users. 6,8,12 Similar studies would need to be conducted in feline populations to establish or deny a causative role for ETS.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Studies in human populations have demonstrated the presence of DNA adducts with tobacco-related carcinogens in neoplasms associated with tobacco use, as well as in the oral mucosal cells of cancer-free tobacco users. 6,8,12 Similar studies would need to be conducted in feline populations to establish or deny a causative role for ETS. It must also be considered that the ETS may alone not be causal but a key exposure in a series of cumulative genomic insults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar linear relationship was also found in bladder cancer biopsies. Immunohistochemistry analysis of human bladder biopsies with an antibody specific to 4-aminobiphenyl (4-ABP)-DNA adducts detected a correlation with staining levels and smoking history (Curigliano et al, 1996). Adduct levels were significantly higher in current smokers (n ¼ 24) than in nonsmokers (n ¼ 22) (Po0.0001).…”
Section: Dna Damage and Repairmentioning
confidence: 98%
“…In fact, our preliminary study showed that certain dietary isothiocyanates could inhibit the formation of 4-aminobiphenyl-DNA adducts in human bladder cancer cells. 4-Aminobiphenyl, a major carcinogen of human bladder cancer derived from cigarette smoking as well as occupational exposure, causes DNA damage and tumorigenic transformation in the bladder (33)(34)(35)(36), and indeed, 4-aminobiphenyl-DNA adducts were detected in a large percentage of human bladder cancer biopsies and were closely correlated to the amount of cigarettes smoked (37)(38)(39). Thus, it is possible that dietary isothiocyanates derived from cruciferous vegetables may be particularly effective in modifying smoking-related bladder carcinogenesis.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%